Pengaruh Religiusitas terhadap Minat Menjadi Nasabah pada Bank Indonesia Provinsi Kalimantan Selatan dengan Syariah Financial Literacy Dan Financial Behavior Sebagai Variabel Mediasi (Studi Kasus pada Bank Syariah Indonesia KCP Tapin) - Hakim, Ahmad Muqarrabin; Solekah, Nihayatu Aslamatis (Universitas Batanghari Jambi, 2024)
Religiosity can be a factor that influences a person's interest in becoming a customer in a sharia banking company, including Bank Syariah Indonesia (BSI). South Kalimantan Province is one of the regions that has the highest religiosity with a Muslim population of 96.7%. Likewise, sharia financial literacy will be one of the determining factors for this interest. Data also shows that the level of sharia financial literacy in South Kalimantan Province always increases every year. Then the financial behavior factor or financial behavior will also increase this interest. The aim of this research is to determine the influence of religiosity on interest in becoming a customer at Bank Syariah Indonesia (BSI) South Kalimantan Province with sharia financial literacy and financial behavior as mediating variables. This research is quantitative in type. The population is BSI KCP Tapin (South Kalimantan) customers with a sample of 190 people. The sampling technique uses non-probability sampling with a purposive sampling method, the data collection technique uses a questionnaire and is processed using SmartPLS and analyzed using partial least squares (PLS) analysis. The results of this research found that partially, religiosity, sharia financial literacy and financial behavior had a direct influence on interest in becoming a BSI KCP Tapin customer with a positive and significant value. Religiosity has a direct effect on sharia financial literacy and religiosity has an indirect effect on interest through sharia financial literacy as a positive and significant mediating variable. Sharia financial literacy has a direct effect on financial behavior and sharia financial literacy has an indirect effect on interest through financial behavior as a mediating variable.